Always communicate a message of positivity. Issue 7 (13th September 2021) - Enos, Gary A.
Abstract : Optimism in the face of the challenges a small private liberal arts institution can encounter characterizes the leadership at Emory & Henry College, located in the highlands of southwest Virginia. Jennifer Pearce, Vice President for Enrollment and External Affairs, considers the can‐do attitude a cornerstone of her leadership style, mirroring the approach she has seen from the college's president, John W. Wells.